The spatial dimension of productivity - Tsvetkova, Alexandra,Ahrend, Rudiger,Oliveira-Martins, Joaquim,Lembcke, Alexander C.,Knutsson, Polina,Jong, Dylan,Terzidis, Nikolaos (OECD, 2020)
This working paper offers a synthesis of the current knowledge on the determinants of productivity. It carefully reviews both “spatial” (e.g. agglomerations, infrastructure, geography) and “aspatial” (e.g. human capital, labour regulations, industry-level innovation and dynamism) productivity drivers and demonstrates how the underlying spatial dynamics behind the latter group makes all productivity determinants “spatial” in nature. The paper demonstrates that productivity is inherently a spatial phenomenon and its understanding without a local/regional dimension is incomplete.
10.1787/ba5edb47-en
Keywords: Amtsdruckschrift; Graue Literatur; Urban; Rural and Regional Development; spatial productivity; productivity growth; local development; cities; regions; industries; firms; places